Children's screentime is associated with reduced brain activation during an inhibitory control task: A pilot EEG study - Lewin, Kaitlin M.; Meshi, Dar; Aladé, Fashina; Lescht, Erica; Herring, Caryn; Devaraju, Dhatri S.; Hampton Wray, Amanda (Frontiers in Cognition, 2023)
Children’s screentime has been linked with a variety of behavioral consequences, including decreased inhibitory control. While children’s screentime is associated with distinct functional brain differences, the links between screentime and neural markers of inhibitory control are unknown. Therefore, we examined these relationships in a pilot study using a Go/No-Go task (N=20). After controlling for age, increased child screentime was significantly correlated with reduced P2 and P3 amplitudes elicited by No-Go trials. No significant relationships were observed with behavioral accuracy or response time. These findings indicate that children with greater screentime exhibit less robust neural processes for inhibitory control. Limitations and future directions are discussed within these preliminary findings.